Murder Ob/Scene: The Seen, Unseen and Ob/scene in Murder Trials - Carolyn McKay (Law Text Culture, 2010)
Tragedies and murder trials explore the relationship between the living and the dead; the present and absent; the seen, unseen and obscene. The central focus of my recent research into viva voce testimony was to consider the role of the live human voice in resuscitating the past crime scene, providing me with the opportunity to observe and interpret murder trials from the perspective of a visual artist who has also studied law. Given my legal background, I was also interested in re-interpreting and deconstructing court procedures, rituals and aesthetics and, through this process, revealing issues of theatricality and the concept of the ob/scene.